Critical perspective on smart thermally self-protective lithium batteries. (November 2022) - Zhou, Jinqiu; Huan, Yunfei; Zhang, Lifang; Wang, Zhenkang; Zhou, Xi; Liu, Jie; Shen, Xiaowei; Hu, Lanping; Qian, Tao; Yan, Chenglin
Graphical abstract: This paper reviews research progress of internal intelligent thermal protection methods to improve thermal safety of lithium batteries. Firstly, through phase separation/transition of electrolytes and thermoregulating separators with phase-change materials or flame retardants, thermal runway could be largely alleviated. However, continuous electrochemical reactions still go on and further heat-generation still exists, thus this kind of strategies can only delay but not eliminate the onset of thermal runaway. Hence, on the other hand, strategies by insulating ionic or current transport to switch off cell reactions when the temperature increases to a high level have also been developed to avoid heat-generation and eradicate possible thermal runaway. Abstract: Thermal safety is one of the most pressing issues facing lithium batteries development, particularly in large-scale battery packs with high power densities. However, traditional external strategies fail to respond immediately to the internal increased heat and pressure. Therefore, it is of great urgency to develop internal control strategies to confer innate thermally self-protective intelligence onto lithium batteries. This paper reviews the research progress of internal intelligent thermal protection methods to improve the thermal safety of lithium batteries. Firstly, through phase separation/transition of electrolytes and thermoregulating separators with phase-change materials or flame retardants, thermal runway could be largely alleviated. However, continuous electrochemical reactions still go on and further heat-generation still exists, thus this kind of strategies can only delay but not eliminate the onset of thermal runaway. Hence, on the other hand, strategies by insulating ionic or current transport to switch off cell reactions have also been developed to avoid heat-generation and eradicate possible thermal runaway. Finally, insights into the future development of smart safer lithium batteries to avoid thermal runaway in terms of consistency, reversibility and adjustability are discussed, offering avenues in the rational design of smart thermally self-protective lithium batteries in the near future.